Intramolecular Diels-Alder reaction of furans with allenyl ethers followed by sulfur and silicon atom-containing group rearrangement - Wu, HJ; Yen, CH; Chuang, CT (My University, 1998)
The intramolecular Diels-Alder reactions of a furandiene with an allenyl ether dienophile followed by the alkylthio, alkylsulfinyl, alkylsulfonyl, and trimethylsilyl group rearrangements are reported. Refluxing the propargyl ether 3 with t-BuOK in t-BuOH at 85 degrees C gave the 1,4-rearrangement product 4 exclusively. The alkylthio group 1,4-rearrangement may proceed intramolecularly via the tight; ion pairs. Refluxing the 5-(alkylsulfinyl)-2-furfuryl propargyl ethers 9a-e and the 5-(alkylsulfonyl)-2-furfuryl propargyl ethers 19a-e under the same reaction conditions gave the alkylsulfinyl group and the alkylsulfonyl group 1,2-rearrangement products 10a-e and 20a-e, respectively. No detectable amount of the corresponding 1,4-rearrangement products 11a-e and 21a-e was obtained. In the cases of 9b and 19b, which possess two furfurylic hydrogen atoms, no detectable amount of the furan ring-transfer reaction products was obtained. Refluxing the 5-(trimethylsilyl)-2-furfuryl propargyl ethers 25a-d with t-BuOK in t-BuOH at 85 degrees C for 10 h gave the trimethylsilyl group 1,2-rearrangement products 26a-d and Brook rearrangement products 27a-d. The reaction mechanisms for these novel intramolecular Diels-Alder reactions are discussed. In the case of 37, which possesses two furfurylic hydrogen atoms, compound 38 was obtained via an intramolecular Diels-Alder reaction followed by the furan ring-transfer reaction and Brook rearrangement.